2008
DOI: 10.1055/s-2007-995691
|View full text |Cite
|
Sign up to set email alerts
|

Transluminal closure for NOTES: an ex vivo study comparing leak pressures of various gastrotomy and colotomy closure modalities

Abstract: Suture (both hand-sewn and endoscopically deployed) appears to produce the strongest closures in both stomach and colon, with the important caveats that (1) a continuous through-thickness suture track be avoided, such as in the full-thickness closure, or (2) suture holes be buried, such as in the purse-string configuration. When suture tracks are full-thickness, they can serve as leak sites. Staples and clips can produce comparable closures, but only under ideal conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 16 publications
1
43
0
1
Order By: Relevance
“…Nevertheless, the leakage pressure of EMFCA is relatively lower than that of standard clips according to the literature [23], which we think is closely related to the mechanism clips close the defect. In this respect, standard clips grab the defect from mucosa, squeezing the mucosal and/or seromuscular tissue, thus resulting in a relatively higher leakage pressure.…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, the leakage pressure of EMFCA is relatively lower than that of standard clips according to the literature [23], which we think is closely related to the mechanism clips close the defect. In this respect, standard clips grab the defect from mucosa, squeezing the mucosal and/or seromuscular tissue, thus resulting in a relatively higher leakage pressure.…”
Section: Discussionmentioning
confidence: 68%
“…No failure or complication of the transorgan defect closure was observed. Other authors reported instead that the technique is sometimes difficult to complete; moreover, approximation obtained by this technique is limited to the mucosal layer [4,5]. For this reason recently an ex vivo study has been published showing that the only way to increase the burst pressure of a gastrotomy closed by standard clips is to create a tunnel in the submucosal layer of at least 8 cm, thereby increasing mean burst pressure from approximately 40 to 87 mmHg [6].…”
Section: Jumbo Endoclipsmentioning
confidence: 99%
“…The activation of linear staplers during endoscopy is relatively easy, while in contrast the manipulation of the tissue within the branches of the device seems extremely difficult, and therefore the technique demanding. In the ex vivo study performed by the group of Thompson [4] a flexible linear stapler by Power Medical Interventions (Langhorne, PA) was employed and compared with various hand-suturing techniques as well as standard endoscopic clipping. The device, although probably used in suboptimal conditions due to inappropriate staple dimensions, proved effective in ex vivo application, being able to obtain considerable burst pressures, comparable to running sutures [26,27].…”
Section: Pmi Surgassistmentioning
confidence: 99%
“…However,o n-going research into closure devices using T-tags and av ariety of mechanical devices is promising. 11,12 Expertise in the full array of closure techniques available will be an essential prerequisitef or the surgeon or gastroenterologist undertaking NOTES.…”
Section: Closurementioning
confidence: 99%